The Rise of Vietnamese Nuns: Views from the Buddhist Revival Movement (1931–1945) - Sinh, Ninh Thị (Religions, 2022)
In this article, with the aim of better understanding the development of Vietnamese Buddhist nuns, the period of the Buddhist revival movement is investigated. This event is considered a turning point for Vietnamese Buddhism. In addition, it will help to shed light on the status of Vietnamese nuns. In this article—which is mainly based on archival documents kept in the National Overseas Archives (the French colonial archives held at the Archives Nationales d’Outre-Mer) and the National Archives Center I, Buddhism periodicals, and memoirs—the status of Vietnamese women during the French colonial period is clarified, as well as the positive effects of the colonial regime in regard to the change in women’s perceptions. Then, the differences in the nuns’ situation in three regions are analyzed. Finally, an exploration is conducted into the rise of nuns during the revival movement and the emergence of reformist nuns. Indeed, it is reformist nuns that have shaped the image of modern Vietnamese nuns. Moreover, they also created a direction by which the following generations could continue along, as well as playing an important role in the Vietnam Buddhist Sangha.